How much time do nurses in Norwegian emergency departments spend on different work tasks with and without a clinical pharmacist present—a time and motion study - Renata Vesela Holis; Beate Hennie Garcia; Elin Christina Lehnbom; Marie Fagerli; Ashrak Majeed; Tine Johnsgård; Birgitte Zahl-Holmstad; Kristian Svendsen; Eirik Hugaas Ofstad; Torsten Risør; Scott R. Walter; Marit Waaseth; et al. (BMC Emergency Medicine)
Abstract Background The emergency department (ED) is a demanding work environment where nurses undertake a variety of clinical and administrative tasks, including medication-related tasks. The integration of a clinical pharmacist into the ED team represents a complex intervention with potential implications for nurses’ distribution of work time, particularly concerning medication-related tasks. This study examined the distribution of work time among ED nurses and assessed the impact of a clinical pharmacist’s presence on this distribution, with an emphasis on medication-related work tasks. Methods A direct observational time and motion study was conducted to evaluate the work time distribution of nurses in three Norwegian EDs, applying the Work Observation Method By Activity Timing (WOMBAT) methodology. Time distributions were measured for non-medication-related tasks, medication-related tasks, standby and movement, both in the absence and presence of a clinical pharmacist in the same ED. Results A total of 298 h of nursing work time were observed, comprising 138 h without pharmacists present and 160 h with pharmacists present. In the absence of a pharmacist, nurses spent 62.7% of their time on non-medication-related tasks, 34.7% on standby and movement, and 3.3% on medication-related tasks. The introduction of a clinical pharmacist did not significantly change the overall distribution of nurses’ work time, although some variations were noted across the EDs. Conclusion ED nurses in three Norwegian EDs dedicated only 3.3% of their work time to medication-related tasks. The presence of clinical pharmacists did not substantially affect the distribution of nurses’ work time.